Pengaruh Asupan Gizi, Aktivitas Fisik, Pengetahuan, dan Sikap Terhadap Status Gizi Remaja SMKN 1 Penawartama Tulang Bawang - Firdawati Firdawati; Zukryandry Zukryandry; Kiki Puspasari; Andra Vidyarini; Nathasa Khalida Dalimunthe (HB PRESS, 2025)
Proper nutrition is essential for adolescents to ensure they grow and develop to their full potential. When adolescents don't get enough to eat, it may affect their health and nutritional condition, and those effects can last into adulthood. Teens enrolled in SMKN 1 Penawartama, a public school in Tulang Bawang Regency, Lampung Province, will have their dietary habits, levels of physical activity, nutritional knowledge, and attitudes studied. In order to get nutritional status data, body mass index (BMI) calculations were performed. Two 24-hour food recall questionnaires were used to measure students' dietary consumption, and another set of questionnaires was used to measure their physical activity, nutritional knowledge, and attitudes. Using Fisher's Exact Test, we examined the data to find out how dietary consumption, exercise, nutritional awareness, and attitudes affected nutritional status. Although they have a strong understanding of nutrition and a positive mindset, the majority of students do not get enough exercise and eat poorly. The bivariate analysis did not uncover any correlation between the students' nutritional status and their carbohydrate, protein, fat, physical activity, knowledge, or attitude intakes (p = 0.572, p = 0.645, p = 109, p = 0.649, respectively). The results of this study did not find any significant association in the variables analyzed, so further research is recommended to assess what factors are related to the nutritional status of adolescents with more respondents in various different school environments to see a broader picture of nutrition in adolescents.